Getting Justice through Legal Assistance: A Comparing Case of Indonesia and Malaysia - Maala, Riyun Khilmawati (The Indonesian Journal of International Clinical Legal Education, 2021)
Equality before the law should be applied to all citizens impartially. However, there are still discriminatory cases against those who are in lower strata than others. So we need a legal revolution that guarantees the fulfillment of justice which is then used as a source in law enforcement practices, legal protections, and legal services for poor people or groups. In addition to Indonesia, the State of Malaysia is also trying to provide justice for all its citizens by trying to provide legal aid guarantees for its citizens who are experiencing legal problems but are not able to afford it economically. This research is intended to analyze the legal comparison of the implementation of legal aid in the State of Indonesia and the State of Malaysia for the sake of creating justice. The research also aims to find out what obstacles are encountered in the implementation of legal aid in the State of Indonesia and the State of Malaysia for the sake of creating justice.